Sophytes and the Mirage of an ‘Indian’ Weight Standard - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2022)
For more than 150 years numismatic scholarship postulated that a coinage associated with Sophytes was struck on an ‘Indian’ weight standard. Despite mounting evidence to the contrary, this evolved into an enduring mirage, accompanied by an added dimension of complexity, one that posited that the coinage was struck simultaneously on two weight standards, Attic and ‘Indian.’ This mirage, and its associated complexity is dispersed completely by a comprehensive metrological analysis of 957 coins across seven silver denominations in the coinage of Sophytes, and his predecessor Andragoras, struck in Parthia during the period 250s-238 BC. It confirms that eleven series of issues in the coinage constitute a single currency system, an epichoric coinage that was systematically weight adjusted based on a reduced Attic weight standard tetradrachm of 17.00 grams, with an increased component seigniorage, up to fifteen percent, applied to the smaller denominations. This metrology is reflective of its origin in the mid 3rd century BC.